P212 Understandings and responses to joint pain: preliminary findings from a rapid ethnographic assessment in Northern Tanzania. (23rd April 2022) - Msoka, Elizabeth F; Bunn, Christopher; Msoka, Perry; Yongolo, Nateiya M; Laurie, Emma; Wyke, Sally; McIntosh, Emma; Mmbaga, Blandina
Abstract: Background/Aims: Musculoskeletal disorders (MSKD) are an important global health problem, but we know little about how it is understood and explained in Tanzanian communities. This understanding is crucial for developing culturally competent interventions and services for MSKD which avoid unintended impacts. This study aims to examine how joint pain is understood, explained, and responded to in rural and peri-urban communities in northern Tanzania. Methods: We conducted rapid ethnographic assessment (REA) in two communities in Kilimanjaro region (one peri-urban, one rural) to document the language used to describe joint pain, ideas about causes, understandings of who experiences such pain, the impacts the pain has and how people respond to it. The REA included 60 short interviews with community leaders, traditional healers, community members, and pharmacists. The research team also wrote detailed field notes and, with written consent, took photographs which were used to develop 'thick descriptions' of the phenomena in each community. Thematic analysis of interview notes, thick descriptions and photographs was conducted using QDA Miner (v5.0) software. Results: The dominant concepts of joint pain and its cause were named as Ugonjwa wa baridi - cold disease; Ugonjwa wa uzee - old age disease; rimatizim - disease of the joints and g auti - gout. Causes mentioned included exposure to the cold - walking bare foot, working in cold conditions - old age, alcohol and red meat consumption, witchcraft, demons, settling in one position, sex, injuries/falls. Age, gender and occupation were seen as important factors for developing joint pain. The impacts of joint pain included loss of mobility, economic and family problems, death, reduction in sexual functioning, and negative self-perceptions. Responses to joint pain blend biomedical treatments, exercise, herbal remedies, consultations with traditional healers and religious ritual. Conclusion: Understandings of and responses to joint pain in the two communities are 'syncretic' - mixing folk and biomedical practices. Narratives about who is affected by joint pain mirror emerging epidemiological findings, suggesting a strong 'lay epidemiology' in these communities. The impacts of joint pain are wide ranging, extending beyond the individual affected, and suggest that there are unmet needs which can be targeted by future interventions and services. Disclosure: E.F. Msoka: None. C. Bunn: None. P. Msoka: None. N.M. Yongolo: None. E. Laurie: None. S. Wyke: None. E. McIntosh: None. B. Mmbaga: None.